Highly selective and sensitive colorimetric chemosensor based on tricarboyanine for detection of Ag+ in industrial wastewater - Xiaolong Zeng; Xuezhao Li; Wen Sun (Journal of Leather Science and Engineering, 2020)
Abstract An efficient fluorescent probe 1 based on tricarbocyanine derivative was designed and synthesized, which can detect Ag+ in real industrial wastewater. UV-Vis absorption and fluorescent emission spectra of probe 1 were carried out and indicated this probe can bind Ag+ via complexation reaction, then leading to a remarkable color change from blue to light red. Furthermore, probe 1 showed high sensitive performance and excellent selectivity toward Ag+ over other common metal ions in neutral pH. The sensing mechanism was proposed and further confirmed by 1H NMR, which demonstrate analyte-induced destruction of the π-electron system could be shorten by the disruption of the pull-push π-conjugation system in probe 1. Moreover, a test strip was prepared by filter paper immersing in probe 1 solution, which further provide its potential application for trace Ag+ detection in real industrial wastewater. Graphical abstract